Desensitizing agents' post-bleaching effect on orthodontic bracket bond strength - Pamungkas, Gufa Bagus; Karunia, Dyah; Suparwitri, Sri (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Nowadays, many patients wanting to bleach and do orthodontic treatment simultaneously, in-office bleaching is more favorable because of the instant results. However, in-office bleaching procedures result in severe enamel surface demineralization and decreasing the attachment of the orthodontic bracket. Applying a desensitizing agent after in-office bleaching can remineralize the enamel surface. There are two types of desensitizing agents: Fluoride-based and non-fluoride-based. Purpose: This study aims to analyze the effect of applying fluoride-based and non-fluoride-based desensitizing agents after in-office bleaching on orthodontic brackets. Methods: Twenty-seven post-extraction upper premolars were divided into three groups (n=9): Control group, fluoride-based group, and non-fluoride-based group. The samples were subjected to an in-office bleaching procedure before a fluoride desensitizing agent was applied to the fluoride group and a non-fluoride desensitizing agent was applied to the non-fluoride group. Then, a brackets bonding procedure was performed on all samples. The samples were tested for shear bond strength (SBS), and the adhesive remnant index (ARI) was measured. The data was analyzed by a one-way analysis of variance on the SBS test, while the ARI scores were analyzed by the Kruskal–Wallis test. Results: The fluoride and non-fluoride groups showed a significantly increased SBS of the brackets after in-office bleaching (P < 0.05), with the fluoride-based desensitizing agent having the highest SBS score, while the ARI scores had an insignificant difference between all groups (P > 0.05). Conclusion: The application of desensitizing agents after in-office bleaching increased the metal brackets' SBS but could not change the ARI scores.